Tratamento das questões ambientais na escola: um trabalho de conscientização com alunos e professores no contexto da modelagem - Barrozo, Elane Cristina Guimarães Marinho (2017)
Today, mankind's living standards are interfering with the quality of the environment. The planet has been suffering major environmental impacts due to the excessive exploitation of natural resources. Faced with this picture, one can see the need to develop a sense of environmental preservation in society. Although not the only school, it can be considered the main means for the formation of individuals responsible and aware of their rights and duties. The present work investigated how environmental issues are treated in a public school in Baixada Fluminense in order to collaborate in the development of critical thinking among students and teachers. For that, the modeling contributions were used. The research was developed in a qualitative approach of the research-teaching type and counted with the participation of 52 students and 22 teachers of the Parada Angélica State College - Duque de Caxias - RJ. For the collection of data and evidence, survey questionnaires and a suggestion box were used to identify the themes related to this area of greatest interest. The results show that this school is open to the work of environmental education, but many teachers reported difficulties in working on this theme in a transversal way, which demonstrates the need for more investment in continuing education for these professionals. The discussions generated from the modeling work contributed to the reflection and the exchange of knowledge, which resulted in the creation of an environmental newspaper with news and information about the environment and related problems. This construction favored the development of a collective and interdisciplinary work, increasing the interest of those involved in research, reading and writing. In addition to the newspaper, teachers committed to develop an environmental project in school every school year. It is understood that to the extent that the school becomes susceptible to dialogue and world reading, students are encouraged to develop critical thinking in order to act as responsible citizens in the society in which they live. This work contributed to a greater clarification on current environmental problems and on the contributions of modeling in the treatment of these issues.